PENGARUH KONSUMSI MINUMAN JAHE TERHADAP MUAL MUNTAH PADA IBU HAMIL TRIMESTER - Amran, Rovita; Isnaini, Nurul; Utami, Vida Wira; Yantina, Yuli (Universitas Malahayati Bandar Lampung, 2021)
Background Nausea, vomiting in pregnancy is generally called emesis gravidarum, experienced by around 70-80% of pregnant women and is a phenomenon that often occurs at 5-12 weeks of gestation. The feeling of nausea in early pregnancy can be reduced by using complementary therapies such as herbs or traditional herbs that are easily obtained such as ginger. A survey conducted in January 2019 by looking at the book visit of Pregnant Women There were 231 Pregnant Trimester I Pregnant Women, and 187 people who had emesis gravidarum (81%). The purpose of this study is to find out the effect of ginger drink on vomiting nausea in first trimester pregnant women at UPT Puskesmas Kupang Kota Kecamatan Teluk Betung Utara Bandar Lampung City in 2019.This type of research is quantitative, the research design used in this study is OnemGroup Pretest-Postest Design. The population in this study were all pregnant women who experienced nausea and vomiting as many as 187 respondents. Sample 32 people, the sampling technique used was purposive sampling. Data collection using the Rhodes Index Scale sheet and data analysis used was the T-dependent test.The results of the study revealed that the average value of nausea and vomiting before consumption of 17,718 ginger drinks and a standard deviation of 1,954. The average value of Nausea and vomiting after consumption of 6,843 ginger drinks and a standard deviation of 1,297. Conclusion Effect of Ginger Drink Consumption on Nausea and Vomiting in TM I pregnant women (p value 0,000 <0.05). Suggestions For pregnant women to be able to take advantage of herbal plants such as ginger in dealing with nausea, vomiting Keywords: Nausea Vomiting, Ginger Drink ABSTRAK Latar Belakang Mual muntah pada kehamilan umumnya disebut emesis gravidarum, dialami sekitar 70-80% wanita hamil dan merupakan fenomena yang sering terjadi pada umur kehamilan 5-12 minggu. Rasa mual pada awal kehamilan dapat di kurangi dengan menggunakan terapi komplementer antara lain dengan tanaman herbal atau tradisional yang mudah di dapatkan seperti jahe. Survey yang lakukan pada januari Tahun 2019 dengan melihat buku kunjungan Ibu Hamil Terdapat Ibu Hamil Trimester I sebanyak 231 ibu hamil, dan yang mengalami emesis gravidarum sebanyak 187 orang (81%).Tujuan penelitian adalah Diketahui Pengaruh Minuman Jahe Terhadap Mual Muntah pada ibu hamil trimester I di UPT Puskesmas Kupang Kota Kecamatan Teluk Betung Utara Kota Bandar Lampung Tahun 2019.Metode Penelitian jenis kuantitatif, Desain penelitian yang digunakan dalam penelitian ini adalah One Group Pretest-Postest Design. Populasi dalam penelitian ini adalah seluruh ibu hamil yang mengalami mual muntah sebanyak 187 responden. Sampel 32 orang, Teknik sampling yang di gunakan purposive sampling. Pengumpulan data dengan menggunakan lembar Skala Indeks Rhodes dan analisa data yang digunakan adalah uji T-dependent.Hasil penelitian diketahui Nilai rata-rata Mual muntah sebelum Konsumsi Minuman Jahe 17.718 dan standar deviasi 1.954. Nilai rata-rata Mual muntah Setelah konsumsi minuman jahe 6.843 dan standar deviasi 1.297.Kesimpulan Ada Pengaruh Pemberian Konsumsi minuman jahe terhadap mual muntah pada ibu hamil TM I (p value 0,000 < 0,05).Saran Bagi ibu hamil dapat agar dapat memanfaatkan tumbuhan herbal seperti jahe dalam mengatasi mual muntah. Kata Kunci : Mual Muntah, Minuman Jahe